2011
DOI: 10.1016/j.ejvs.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Distal versus Ultradistal Bypass Grafts: Amputation-free Survival and Patency Rates in Patients with Critical Leg Ischaemia

Abstract: This study show that both distal and ultradistal bypass have comparable outcome regardless of the co-morbidities. The authors believe that elderly patients should be offered ultradistal bypass if indicated to avoid major amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…Technical details of the bypass procedure have been published previously. Preoperative duplex imaging was used to identify a venous conduit where possible, with the great saphenous vein (GSV) as the preferred conduit, followed by the short saphenous vein (SSV) or arm veins (cephalic and basilic veins).…”
Section: Methodsmentioning
confidence: 99%
“…Technical details of the bypass procedure have been published previously. Preoperative duplex imaging was used to identify a venous conduit where possible, with the great saphenous vein (GSV) as the preferred conduit, followed by the short saphenous vein (SSV) or arm veins (cephalic and basilic veins).…”
Section: Methodsmentioning
confidence: 99%
“…Grafts with diameter less than 3.5 mm and smaller length have 50% probability for patency at least 1 year, if constructed above relatively healthy arterial segment, while a graft with larger diameter and bigger length -36%. Some studies have shown that poor run-off affects negatively the patency of infrainguinal reconstructions [30][31][32]. Patency of infrainguinal bypass and subsequent limb salvation depend crucially on the quality of the distal arterial segment.…”
Section: Discussionmentioning
confidence: 99%
“…Angioplasty and bypass are regarded not as competing but as complementary treatments. Also, a recent study has shown that both distal and ultra‐distal bypass have comparable outcomes regardless of the comorbidities . After either angioplasty or bypass, patients are followed up closely in the Diabetic Foot Clinic to assess the clinical outcome and the need for further intervention.…”
Section: The Multidisciplinary Diabetic Foot Teammentioning
confidence: 99%